Older adults with Alzheimer's disease: a systematic review about the Occupational Therapy intervention in changes of performance skills. - Dias Bernardo, Lilian (Brazilian Journal of Occupational Therapy / Cadernos Brasileiros de Terapia Ocupacional, 2018)
Introduction: Older adults with Alzheimer's disease present restrictions on engagement in occupations that may be associated with changes in performance skills. Objective: To identify and analyze the scientific production of Occupational Therapists interventions in the care of older adults with Alzheimer's disease who present changes in performance skills. Method: A systematic review was conducted, in a 10-year period (2006-2015), in English, Portuguese, and Spanish. The Web of Science, MEDLINE/PubMed, CINAHL, PsycINFO®, LILACS, SciELO, OTSeeker, and PEDro databases were used as sources of information. To search, the descriptors "Alzheimer Disease" and "Occupational Therapy" were used, which were combined with "behavior", "environment", "cognition" and "social support", using the boolean operators AND or OR. There were 13 articles identified that met the inclusion criteria selected for deeper analysis: scientific publications related to Alzheimer's disease in older adults, that approach interventions directed to performance skills, with the participation of at least one occupational therapist as an author, and without restrictions on the stage of the disease. Results: No national study was found. The identified interventions are directed toward emotional regulation, motor skills, and procedural skills. In their acting, occupational therapists use route navigation, external aid devices (calendars), computer activities and multisensory stimulation as therapeutic resources that attest the effect of the interventions in motor learning, spatial orientation or in the reduction of neuropsychological symptoms and/or behavioral changes. Conclusion: The publications are related to the intervention practices for the improvement of the older people functional capacity and emotional regulation. However, Brazilian Occupational Therapists face the need to publish interventions to justify the effectiveness of their actions and their insertion in shared professional practice, at the different attention levels to the health of older people.